2021
DOI: 10.3748/wjg.v27.i15.1595
|View full text |Cite
|
Sign up to set email alerts
|

Abelson interactor 1 splice isoform-L plays an anti-oncogenic role in colorectal carcinoma through interactions with WAVE2 and full-length Abelson interactor 1

Abstract: BACKGROUND Expression of the full-length isoform of Abelson interactor 1 (ABI1), ABI1-p65, is increased in colorectal carcinoma (CRC) and is thought to be involved in one or more steps leading to tumor progression or metastasis. The ABI1 splice isoform-L (ABI1-SiL) has conserved WAVE2-binding and SH3 domains, lacks the homeo-domain homologous region, and is missing the majority of PxxP- and Pro-rich domains found in full-length ABI1-p65. Thus, ABI1-SiL domain structure suggests that the protein ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Studies have also shown that TGF-β1 mediates WAVE2 upregulation on hepatic stellate cell (HSC) activation and promotes activated-HSCs metastasis. Thus, these findings imply that WAVE2 plays a critical role in colorectal liver metastasis [ 60 , 61 , 62 , 63 ].…”
Section: Role Of Wave2 In Cancermentioning
confidence: 99%
“…Studies have also shown that TGF-β1 mediates WAVE2 upregulation on hepatic stellate cell (HSC) activation and promotes activated-HSCs metastasis. Thus, these findings imply that WAVE2 plays a critical role in colorectal liver metastasis [ 60 , 61 , 62 , 63 ].…”
Section: Role Of Wave2 In Cancermentioning
confidence: 99%
“…Previous studies showed that the abnormal expression and phosphorylation of ABI1 are involved in the invasion and metastasis of various malignant tumors (colorectal cancer, gastric cancer, pancreatic cancer, hepatocellular carcinoma, breast cancer, leukemia, prostate cancer, and ovarian cancer, etc. ), being closely related to their prognosis [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The human ABI1 gene is located at chromosome 10p11.2, and its pre-mRNA can be spliced into at least 12 different ABI1-TSVs. They encode twelve different protein isoforms, and their significant differences in functional domains suggest that the regulation of ABI1-TSVs in pathophysiological processes may be meticulous and complex [ 8 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that ABI1 is highly expressed in CRC tissues [ 7 ]. In addition to abnormal expression, different transcriptional variants (TSVs) of ABI1 may perform distinct biological functions [ 8 ]and play an important role in the progress of CRC metastasis [ 6 , 9 ]. There are eighteen TSVs generated from ABI1 primary transcript by alternative splicing ( https://www.ncbi.nlm.nih.gov/gene/10006 ).…”
Section: Introductionmentioning
confidence: 99%